Detection of barium 6 sng→6 snh, 6 sni, and 6 snk microwave transitions using selective excitation to autoionizing states - E. G. Kim (2018)
We use selective laser excitation to an autoionizing state to observe the microwave transitions of Ba from the 6sng Rydberg states to the 6snh, 6sni, and 6snk states for 15≤n≤18. We extract the dipole and quadrupole polarizabilities of Ba+ from the measured intervals of the Ba 6sn states of 5 using a nonadiabatic core polarization model. The values we determine for the dipole and quadrupole polarizabilities are αd=124.81(25)a03 and αq=2478(50)a05, respectively. © 2014 American Physical Society.